233k views
4 votes
6x+6=6(x-1) is what I need help with


User Driax
by
4.9k points

2 Answers

3 votes

Hey there!☺


Answer:\boxed{\text{There are no solutions.}}


Explanation:


6x+6=6(x-1)

6x + 6 = (6)(x) + (6)(-1) Distribute

6x + 6 - 6x = 6x - 6 - 6x Subtract 6x from both sides

6 = -6

6 - 6 = -6 - 6 Subtract 6 from both sides

0 = -12

No solutions.

Hope this helps!

User Mahendran Candy
by
5.0k points
1 vote

Steps to solve:

6x + 6 = 6(x - 1)

~Distribute left side

6x + 6 = 6x - 6

~Subtract 6 to both sides

6x = 6x - 12

~Subtract 6x to both sides

0 = -12

No solutions.

Best of Luck!

User Yukulelix
by
4.7k points